Natural Wonders - Brewster, Edwin Tenney, 1866-1960 (Salt Lake City, UT : Project Gutenberg, 2015)
"Natural Wonders" by Edwin Tenney Brewster is a children's educational book that was written in the early 20th century. The work aims to provide young readers with an understanding of natural science concepts, specifically relating to animals, plants, and the processes of life. Brewster presents various scientific topics in a manner accessible to children, encouraging them to explore and appreciate the wonders of the natural world. The opening portion of "Natural Wonders" introduces the subject matter with a focus on the fascinating processes of life cycles, beginning with how a chicken hatches from an egg. Brewster vividly describes the hatching process, detailing the physical changes that occur within the egg over time. He emphasizes the wonder of nature and sets the tone for an engaging exploration of topics such as the characteristics of eggs from different animals and the broader theme of life$1 (Bs continuity across species. The introductory content establishes a foundation for the reader, indicating that the book will answer fundamental questions about how living beings grow and develop, fostering curiosity and learning. (This is an automatically generated summary.)s
Release date is 2015-01-13
Produced by Roger Frank
Keywords: Natural history -- Juvenile literature; Physiology -- Juvenile literature; Biology -- Juvenile literature; Nature -- Juvenile literature